CHARACTERISTICS OF PEDESTRIAN PATHS IN MAKASSAR CITY WHICH ARE ENVIRONMENTALLY FRIENDLY IN THE INTEGRATED CENTRAL BUSINESS DISTRICT (International Conference on Social and Islamic Studies, 2022)
Increased activity in the Central Integrated Business Area in Makassar City, especially the use of the integrated pedestrian path in the Karebosi field and its surroundings, is not equipped with the provision of adequate facilities and infrastructure, resulting in the degradation of spatial functions, along with the increase in community mobility. The method used is a survey method with a collaborative approach which will be described quantitatively and qualitatively, with the aim of knowing the characteristics of the pedestrian path in the area, formulating the general concept of an environmentally sound pedestrian path. The research focus is located on the integration of the Karebosi field pedestrian path and its surroundings. Based on the analysis and discussion, it is obtained that the physical characteristics of the pedestrian path are determined by the factors of comfort, safety and patterns, along with their activities that have not worked effectively. In some segments of the pedestrian path, it is used as a parking area and there are temporary office activities in segment A (Kartini street) which is connected to segment B (Kajaolalido street). For the application of the environment on pedestrian paths, in general the concept can be rearranged several lanes indicated to be a barrier factor, as well as developing aspects that refer to the embodiment of P2KH.